Pengaruh Metode Bahtsul Masa’il terhadap Hasil Belajar Santri dalam Pembelajaran Al-Qur’an Hadis Kelas XI di Pondok Pesantren Asy-Syarif Sidang Koto Laweh - Rayyan, Zuhall; Junaidi, Junaidi (Lembaga Yasin AlSys, 2025)
This study is motivated by the low learning outcomes of eleventh-grade santri in the Al-Qur’an Hadist subject at Pondok Pesantren Asy-Syarif Sidang Koto Laweh, attributed to educator-centered instruction and the limited active participation of santri during the learning process. The research aims to examine whether the use of the Bahtsul Masa’il method results in better learning outcomes compared to conventional methods in Al-Qur’an Hadist instruction. A quantitative approach with a quasi-experimental design was employed, in which the independent variable is the Bahtsul Masa’il method and the dependent variable is the santri's learning outcomes. The study population comprised all students at the MA level, totaling 85 individuals. A simple random sampling technique was used to select 14 santri from class XI.S as the control group and 18 santri from class XI.A as the experimental group. The data collection instrument consisted of a written test with fifteen essay questions. The analysis results indicate a significant effect of the Bahtsul Masa’il method on learning outcomes, contributing 11.64%, as demonstrated by a t-test with a significance value of 0.004 < 0.05. The difference in average final scores shows that the experimental class achieved higher learning outcomes than the control class. Meanwhile, 88.36% of the outcomes were influenced by other relevant factors such as increased critical thinking, participation, and learning motivation among santri. These findings suggest that the Bahtsul Masa’il method is effective in enhancing learning outcomes and promoting more active and meaningful learning.